UNLOCKING KNOWLEDGE: THE IMPACT OF SERVANT LEADERSHIP, UNIVERSITY CULTURE, AND FACULTY COMMITMENT ON KNOWLEDGE SHARING - Nursaimatussaddiya, Nursaimatussaddiya; Maipita, Indra; Cen, Cia; Sari, Dian; Ekawati, Yuni (Faculty of Economic and Business, University of Pasundan, 2025)
This research is motivated by service leadership, higher education culture, commitment, knowledge sharing performance at the North Sumatra Polytechnic. This research was conducted at the Region I Polytechnic of North Sumatra. The aim of this research is to analyze and study descriptively and verifiably the influence of service leadership, higher education culture, and lecturer commitment to the dissemination of knowledge and empowerment on lecturer performance. The research method used is a quantitative method carried out descriptively and verified. The sampling technique was carried out using proportional stratified random sampling. Data sources from primary and secondary data through observation and distribution of questionnaires. The data analysis technique used is SEM. Verifiable research results show that service leadership, higher education culture, and commitment have a positive and significant effect on the dissemination of knowledge.